SWOT Analysis in Determining Consumer Preferences For Designing Traditional Nias Clothing - Lisan Cermin Hati Zebua; Martha Surya Dinata Mendrofa; Maria Magdalena Bate’e; Jeliswan Berkat Iman Jaya Gea (Golden Ratio of Data in Summary, 2024)
The purpose of this research is to find out consumer preferences in designing traditional Nias clothing, find out the design after conducting a SWOT analysis, and find out the obstacles that exist in the process of making traditional Nias clothes. This research uses a qualitative research approach. The sample in this study were 6 people consisting of business owners, traditional leaders, employees, and consumers. Data collection techniques, namely interviews and observations. The results of this study are steps in determining consumer preferences in designing traditional Nias clothing at UD. Vivi is the determination of the size motif and type of material, color selection based on market demand, the design produced by UD. Vivi in designing Nias traditional clothing is seen in terms of shape, size, quality, and product durability, the findings of threats to UD. Vivi is that it can come from various factors, namely competition, changes in market trends, changes in consumer preferences, especially among the younger generation who may prefer clothes with modern styles rather than traditional ones, which can reduce demand for traditional Nias clothing, the influence of foreign cultures: Influence from outside culture, and the tools used are still traditional.